2012
DOI: 10.1039/c2ob07161d
|View full text |Cite
|
Sign up to set email alerts
|

Deracemization of unnatural amino acid: homoalanine using d-amino acid oxidase and ω-transaminase

Abstract: A deracemization method was developed to generate optically pure L-homoalanine from racemic homoalanine using D-amino acid oxidase and ω-transaminase. A whole cell reaction using a biphasic system converted 500 mM racemic homoalanine to 485 mM L-homoalanine (>99% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
(14 reference statements)
0
28
0
Order By: Relevance
“…Recently Deracemization of racemic homoalanine to its optically pure enanti omer was recently examined [49]. The d-AAO used was catalyzing the oxidation of rac-homoalanine to 2-ketobutyrate followed by the conversion to l-homoalanine with ω-transaminase using benzylamine as an amino donor.…”
Section: Deracemization and Dynamic Kinetic Resolution Of Canonical Amentioning
confidence: 99%
“…Recently Deracemization of racemic homoalanine to its optically pure enanti omer was recently examined [49]. The d-AAO used was catalyzing the oxidation of rac-homoalanine to 2-ketobutyrate followed by the conversion to l-homoalanine with ω-transaminase using benzylamine as an amino donor.…”
Section: Deracemization and Dynamic Kinetic Resolution Of Canonical Amentioning
confidence: 99%
“…To solve this 7 problem, we have recombinated the DAAO by fusion to an elastin-like polypeptide 8 (ELP), which was used as the tag to purify the expressed DAAO. ELP-DAAO can be 9 purified through inverse transition cycling (Meyer et al, 1999;Banki et al, 2005), 10 and very good purity can be obtained. It has also been found that ELP-DAAO did not 11 precipitate during the purification process as well as the period of storage, having a 12 very good solubility in aqueous solutions.…”
mentioning
confidence: 97%
“…9 2.5. Enzyme assay and analyses 10 The specific activity of the enzymes was calculated by measuring the formation of 11 pyruvate concentration in the medium, following the methods described in articles 12 (Erikson et al, 2004; Biagi et al, 2012). One unit of enzyme activity is defined as the 13 turnover of one micromole of substrate per minute.…”
mentioning
confidence: 99%
“…D-Amino oxidase from Rhodotorula gracilis (DAAO), a FAD dependent enzyme, was fused to Vitreoscilla hemoglobin (VHb) to form VHb-DAAO. [106] This protein improved the activity and stability of DAAO, and achieved the stereospecific oxidation of D-homoalanine to the corresponding imine, which was further hydrolyzed to form the keto acid intermediate. This…”
Section: Scheme 16mentioning
confidence: 99%